Penanaman Budaya Literasi Mahasiswa (Studi Kasus Pada Mahasiswa Program Studi PPKn FKIP Unkhair) - Umiyanur Latuamuri; Wahyudin Noe; Irwan Abbas (Jurnal Geocivic, 2022)
The background of this research is to instill reading habits and interest in Civics students. The aims of this study were (1) To find out efforts to instill a culture of literacy in PPKn FKIP Unkhair students. (2) To find out the supporting and inhibiting factors of efforts to instill a literacy culture in PPKn FKIP Unkhair students. This study uses a qualitative aprroach and the subjects of this are students of the 2018 2019, 2020, and 2021 PPKn study programs. Data collection techniques consist of observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and conclusion drawing/verification. The results of this study indicate that (1) Efforts to instill a literacy culture in PPKn students have been carried out quite well, this can be seen from several things, including: 1) Giving assignments by lecturers and then followed by group discussion activities. This also encourages students to read and seek information from various sources and hone students' thinking power through questions and answers in discussion forums. 2) Organizing various agendas of activities related to literacy such as public lectures, guest lectures, focus group discussion dialogues and so on. (2) First, the supporting factors in instilling a literacy culture for PPKn FKIP Unkhair students are: 1) The existence of a reading room in the FKIP environment is one of the infrastructures for supporting student reading activities 2) The positive attitude of students towards reading culture. Second, the inhibiting factors for cultivating a literacy culture in PPKn Student consist of internal factors and external factors. Internal factors include: 1) The low reading interest of students as seen from the reading frequency of students who only spend 15 minutes-4 hours a week on average 2) The limited collection of students' personal books 3) The low level of visits by PPKn students to the FKIP reading room, even the majority of PPKn students have never been to the Unkhair library. External factors are as follows: 1) The minimum number of collections of books related to the basic science of Civics in the reading room of FKIP Unkhair; 2) The variety and quality of books in the reading room of FKIP Unkhair is inadequate. Most of the books available are old publications and not the newest ones. 3) The availability of a special reading room for the Civics Study Program which is still combined with the lecturer's room makes the space for students to read is limited 4) The number of collections of reading materials in the PPKn Study Program library is still limited. Keywords :literacy culture ppkn student